Subglottic stenosis in children: Our experience at a pediatric tertiary center for 8 years in South Korea. (June 2019) - Lee, Jin-Choon; Kim, Min-Sik; Kim, Dong-Jo; Park, Da-Hee; Lee, IL-Woo; Roh, Hwan-Jung; Lee, Byung-Joo; Kim, Young-A.; Ko, Sunghwa; Sung, Eui-Suk
Abstract: Objective: The incidence of SGS has been reported to be less than 8% after endotracheal intubation. Therefore there is an increasing trend in the number of patients with acute acquired SGS due to mechanical ventilation in the intensive care unit. However, there have been no reports describing the treatment of SGS in children in South Korea. The objective of this study was to evaluate the management and outcomes of children with SGS at a pediatric tertiary center in South Korea over an 8-year period. Methods: All patients underwent microlaryngobronchoscopy (MLB) with bougination, incision using cold knife or laser and balloon dilatation. Data on age, sex, grade of SGS, number of management interventions, tracheostomy, comorbidities, mean follow-up period, complications, and outcome were reviewed from patient medical charts. Results: Twenty patients (13 [65%] males, 7 [35%] females; mean [±SD] age at the diagnostic procedure 15.26 ± 22.54 months) underwent MLB between March 2009 and December 2017. According to the Myer-Cotton scale, twelve of the 20 (60%) patients had grade III SGS, 7 (35%) had grade II and 1 (5%) had grade 1; there were no patients with grade IV SGS. Nine (45%) patients were diagnosed with acute SGS, and 11 (55%) with chronic SGS. Patients with SGS underwent MLB with interventions (mean 2.41 ± 2.23 per patient). Tracheostomy was performed in 13 of 20 (65%) patients, 2 of 9 (22.2%) with acute SGS, and 11 of 11 (100%) with chronic SGS. Two of 13 (15.3%) patients underwent successful decannulation. One of 2 (50%) patients with acute SGS underwent successful decannulation. Seven of 9 (77.7%) patients with acute SGS underwent MLB only without tracheostomy. Conclusions: In patients with acute acquired SGS, the outcome was good due to the lower rate of tracheostomy and higher decannulation rate. Therefore, it is recommended that MLB with balloon laryngoplasty be performed at the earliest in patients with acute acquired SGS.